2015
DOI: 10.1111/and.12500
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of aminoguanidine on radiotherapy-induced kidney and testis injury

Abstract: This experimental study was designed to investigate both protective and therapeutic effects of aminoguanidine (AG), on radiotherapy (RT)-induced oxidative stress in kidney and testis. Forty rats were divided into five groups equally as follows: (i) control, (ii) RT, (iii) AG, (iv) AG+RT and (v) RT+AG group. Histopathological findings and biochemical evaluations, including tissue malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione (GSH), total oxidant sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
9
2
Order By: Relevance
“…The reduction in antioxidant enzymes is due to the depletion of enzymes during oxidative stress that occurred as a result of irradiation (Khattab et al 2017). In contrast to studies indicating a decrease in GSH in the kidneys (Ekici et al 2016;Ashry et al 2017), a significant increase in GSH levels in the kidneys and ovaries as a result of γ-radiation was observed in this study. GSH is a major non-enzymatic antioxidant involved in the cell defense system against oxidative damage, directly as a free radical scavenger or indirectly by repairing the initial damage to macromolecules being able to maintain protein and nonprotein SH group in a reduced way (Ross 1988;Scibior et al 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…The reduction in antioxidant enzymes is due to the depletion of enzymes during oxidative stress that occurred as a result of irradiation (Khattab et al 2017). In contrast to studies indicating a decrease in GSH in the kidneys (Ekici et al 2016;Ashry et al 2017), a significant increase in GSH levels in the kidneys and ovaries as a result of γ-radiation was observed in this study. GSH is a major non-enzymatic antioxidant involved in the cell defense system against oxidative damage, directly as a free radical scavenger or indirectly by repairing the initial damage to macromolecules being able to maintain protein and nonprotein SH group in a reduced way (Ross 1988;Scibior et al 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…The antioxidant enzymes reduced because of the depletion of enzymes during oxidative stress caused by the irradiation (Khattab et al, 2017;Mansour et al, 2008). In contrast to studies indicating the decreased GSH in the kidney (Cosar et al, 2012;Ekici et al, 2016), the present study showed that GSH concentrations significantly increased in the kidney and ovarium as a result of γ-radiation. Being a main intracellular antioxidant, GSH takes part in the defense system of cells against oxidative damage, directly as a free radical scavenger or indirectly by repairing initial damage to macromolecules and could maintain protein and non-protein SH group in a reduced way (Scibior et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…Many putative LSC biomarkers have been reported ( Table 2 ) including cell cycle regulators, cytoskeletal proteins, cell adhesion molecules, enzymes, growth factors and their receptors, ATP-binding cassette transporters and differentiation associated markers [ 58 , 59 , 60 ].…”
Section: Putative Biomarkers Of Lscmentioning
confidence: 99%